Palladium(0)-catalyzed asymmetric C(sp3)–H arylation using a chiral binol-derived phosphate and an achiral ligand. Issue 2 (19th October 2016) - Yang, Lei; Melot, Romain; Neuburger, Markus; Baudoin, Olivier
Abstract : High enantioselectivities can be achieved using an appropriate chiral base/achiral ligand combination in Pd 0 -catalyzed C(sp 3 )–H activation. Abstract : The first efficient palladium(0)-catalyzed enantioselective C(sp 3 )–H activation reaction using a catalytic chiral base and an achiral phosphine ligand is reported. Fine-tuning the binol-derived phosphoric acid pre-catalyst and the reaction conditions was found to be crucial to achieve high levels of enantioselectivity for a variety of indoline products containing both tri- and tetrasubstituted stereocenters.